AN INTRODUCTION TO THE STUDY OF THE LAW OF THE CONSTITUTION: By A. V. Dicey. Delhi : Universal Law Publishing Co. Pvt. Ltd., Second Indian Reprint, 1998, (NATIONAL CAPITAL LAW JOURNAL, 1997)
NA
Keywords: Parliamentary Sovereignty; Rule of Law; Constitutional Conventions; English Constitution; Legal Supremacy; Judicial Independence; Administrative Law; Political Sovereignty; Constitutional Governance; Democratic Accountability